Distributed speed control for multi-three-phase motors with enhanced power sharing capabilities - Galassini, Alessandro (2018)
This thesis describes the last three years work and the results achieved after several stages of design and experimental validation. The main result is the development of a novel sharing current controller for multi-three-phase electrical machines. The proposed regulator, called "speed-drooped" or simply "droop" controller, allows the current transient triggered by a step change within the rotating reference frame to be controlled. Since multi-three-phase systems appear to be very good candidates for future Integrated Modular Motor Drives and next transportation system challenges, the work has been set up with modularity and redundancy for next future motor drives. During the preliminary stages, the mathematical models of the droop controller have been derived and validated on a multi-drive rig with two three-phase induction motors on the same shaft at the University of Nottingham. After, while developing a new general purpose control platform for power electronics able to control up to three three-phase systems, the Vector Space Decomposition for de-coupling the mutual interactions within multi-three-phase electric motors has been studied. Thanks to it, the inductance matrix of a triple-star two poles synchronous generator at the University of Trieste, Italy, has been diagonalised. Finally, the proposed current controller has been experimentally validated on a nine-phase synchronous generator and compared with the state of the art current sharing techniques. Furthermore, a post-fault compensation strategy has been formulated and validated by means of simulation work. If compared to the state-of-the-art current sharing techniques, the "droop" regulator capability of controlling current sharing transients while keeping constant speed of the shaft has been proven and successfully demonstrated by means of Matlab/Simulink simulations and experiments on both rigs.